2023
DOI: 10.1080/02813432.2023.2178851
|View full text |Cite
|
Sign up to set email alerts
|

Management of child maltreatment suspicions in general practice: a mixed methods study

Abstract: Background Maltreated children have many long-term consequences throughout their lives, but often maltreated children are not recognised in time by professionals. General practice could be central to the early recognition of child maltreatment due to the long-term relationship with families. Objective How do general practitioners (GPs) and practice nurses (PNs) deal with suspected maltreatment in children below 18 years of age, and which factors influence them to report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…An important success factor seems to be the collaboration between midwives, parent advisors, and child healthcare nurses [ 25 ]. The well-functioning family centre is an important meeting point that already before the start of the project included a maternal healthcare centre, the CHS, the social services, and an open preschool in one physical location [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…An important success factor seems to be the collaboration between midwives, parent advisors, and child healthcare nurses [ 25 ]. The well-functioning family centre is an important meeting point that already before the start of the project included a maternal healthcare centre, the CHS, the social services, and an open preschool in one physical location [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although our findings indicate a high level of availability and a strong commitment from PHNs, the Norwegian official reports contends that there are too few reports of child maltreatment and reported cases could have been detected earlier [ 34 , 35 ]. The thorough follow-up described by the PHNs may reflect concerns and uncertainty, which is considered a barrier in reporting child maltreatment [ 27 , 39 , 48 , 51 ]. A Danish study about management of child maltreatment suspicions in general practice found that GPs and practice nurses often felt left to themselves managing their suspicions, especially in cases without clear signs and emphasized the importance of scheduling new appointments as a strategy to track the child's progress and maintaining a relation to the child’s family [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The thorough follow-up described by the PHNs may reflect concerns and uncertainty, which is considered a barrier in reporting child maltreatment [27,39,48,51]. A Danish study about management of child maltreatment suspicions in general practice found that GPs and practice nurses often felt left to themselves managing their suspicions, especially in cases without clear signs and emphasized the importance of scheduling new appointments as a strategy to track the child's progress and maintaining a relation to the child's family [51]. The extensive follow-up may also indicate that PHNs are trying to address the child's needs in other ways than reporting.…”
Section: Discussionmentioning
confidence: 99%
“…GPs are in a unique position to uncover and respond to child abuse [ 7 ] and Norwegian GPs consider themselves to be in a good position to discuss children’s situation in consultations with the parents, when a parent has a medical condition that might affect their caring ability [ 8 ]. Most studies focus on how GPs or primary care workers recognize vulnerability in children and their reporting practice to the CWS [ 9 11 ], and they show that GPs generally underidentify and have a lower reporting rate to the CWS than expected [ 12 – 14 ]. The barriers identified as preventing GPs from contacting CWS are among others structural obstacles such as time pressure and confidentiality, fear of affecting the patient-doctor relationship, negative prejudices against CWS and lack of knowledge about risk factors [ 10 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The barriers identified as preventing GPs from contacting CWS are among others structural obstacles such as time pressure and confidentiality, fear of affecting the patient-doctor relationship, negative prejudices against CWS and lack of knowledge about risk factors [ 10 , 15 , 16 ]. A need for better collaboration between general practice and CWS has been indicated several times [ 11 , 14 , 16 21 ] and there is a lack of intersectoral communication between the health care sector and child welfare sector [ 14 ]. We have not found research that focus directly on a collaborative process between GPs and CWS, although studies have been conducted on GPs’ collaboration with other agencies in the health care sector, such as nurses, pharmacists, mental health workers, physiotherapists and social workers working within the health care sector.…”
Section: Introductionmentioning
confidence: 99%